HTLV-1 HBZ Protein Resides Exclusively in the Cytoplasm of Infected Cells in Asymptomatic Carriers and HAM/TSP Patients - Forlani, Greta; Baratella, Marco; Tedeschi, Alessandra; Pique, Claudine; Jacobson, Steve; Accolla, Roberto S. (Frontiers in Microbiology, 2019)
Human T cell lymphotropic virus type 1 (HTLV-1) is the causative agent of adult T cell leukemia/lymphoma (ATL) and HTLV-1-associated myelopathy/tropical spastic paraparesis (HAM/TSP) in a subset of infected subjects. Two viral proteins, Tax-1 and HTLV-1 basic leucine zipper factor (HBZ) play important roles in the pathogenesis of both diseases. We recently demonstrated that HBZ, previously considered a nuclear protein, is exclusively localized in the cytoplasm of peripheral blood mononuclear cells (PBMCs) of HAM/TSP patients. Here, the analysis of a larger panel of HAM/TSP cases, confirmed that HBZ is a cytoplasmic protein, while Tax-1 preferentially localized in the cytoplasm with fewer speckle-like dots in the nucleus. More importantly, here we report for the first time that HBZ when expressed in asymptomatic carriers (AC), is also confined in the cytoplasm. Similarly, Tax-1 was preferentially expressed in the cytoplasm in a significant proportion of AC. Interestingly both in HAM/TSP and AC patients the expression of HBZ and Tax-1 was rarely found in the same cell. We observed only few cases coexpressing the two oncoprotein in a very limited number of cells. In representative AC and HAM/TSP patients, cells expressing cytoplasmic HBZ were almost exclusively found in the CD4+ T cell compartment and very rarely in CD8+ T cells. Interestingly, at least in the cases analyzed, the expression of THEMIS is dispensable for the cytoplasmic localization of HBZ both in AC and HAM/TSP. The study of an HTLV-1 immortalized cell line established from an HAM/TSP patient confirmed HBZ as resident cytoplasmic protein not shuttling between cytoplasm and nucleus. These results extend our previous observation on the dichotomy of HBZ localization between HAM/TSP and ATL, pointing to the exclusive either cytoplasmic or nuclear localization in the two diseased states, respectively. Moreover, they show a rather selective expression in distinct cells of either HBZ or Tax-1. The unprecedented observation that in AC, HBZ is expressed only in the cytoplasm, strongly suggests a progressive modification of HBZ localization during the disease states associated to HTLV-1 infection. Future studies will clarify whether the distinct HBZ intracellular localization is a marker or a causative event of disease evolution.